A History of Privacy Rights in America: From the Fourth Amendment to the Patriot Act - Twomey, William (Colloquium: The Political Science Journal of Boston College, 2018)
This analysis will trace the development of privacy rights in the United States, beginning with the ratification of the Bill of Rights and ending with the passage of the Patriot Act in 2001. Twomey explores the original constitutional understanding of privacy, tracks the judicial incorporation of privacy as a constitutionally guaranteed right, analyzes how new technologies posed difficult questions for the courts and the legislature, and examines the state of privacy rights directly following the September 11th attacks. This analysis will pay special attention to the Electronics Communications Privacy Act of 1986 (ECPA) and the Foreign Intelligence Surveillance Act of 1978 (FISA) and how these two pieces of legislation altered the state of Americans’ privacy rights in the electronic age.